2020
DOI: 10.1080/14786419.2020.1802271
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial screening of plants from the Brazilian Atlantic Forest led to the identification of active compounds in Miconia latecrenata (DC.) Naudin

Abstract: Antibiotic resistance is a serious global threat to public health. This has promoted the research for new drug targets, and the use of other approaches, such as antimicrobial combined therapy. The present study evaluated the antibacterial activity of 88 extracts from Brazilian Atlantic Forest trees. The organic extract from leaves of Miconia latecrenata (EMl) was the most promising for inhibiting the growth of Staphylococcus aureus (0.3 mg/mL) and Pseudomonas aeruginosa (2.5 mg/mL). After the bioguided fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is the aim of the BIOPROS group that has been implemented a large-scale project to produce and test extracts from the Atlantic Forest trees, where species are still rarely studied for their biological activity. The BIOPROS Extract Library is also screened in other biological targets such as antibacterial [24,25] , Anticholinesterase inhibitor [26] , Insecticidal [27] , and phytonematode control [28] .…”
Section: Resultsmentioning
confidence: 99%
“…It is the aim of the BIOPROS group that has been implemented a large-scale project to produce and test extracts from the Atlantic Forest trees, where species are still rarely studied for their biological activity. The BIOPROS Extract Library is also screened in other biological targets such as antibacterial [24,25] , Anticholinesterase inhibitor [26] , Insecticidal [27] , and phytonematode control [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Four major peaks were observed in the chromatographic profile (▶ Fig. 1 a) and a total of 14 possible withanolides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were tentatively identified in FAv_5 (▶ Table 2), based on the chemical structure, fragmentation pattern, and by comparison with relevant literature data and the Dictionary of Natural Products (DNP) database. MS/MS spectra obtained for each compound are provided in the Supplementary material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In line with our screening for naturally occurring plant-derived extracts, antibacterial and antimelanoma (i.e., murine melanoma B16F10 model) activities, as well as the presence of quinic acid derivatives and flavonoid glycosides, were recently reported in Athenaea velutina (Sendtn.) DʼArcy (Solanaceae) 5 , 6 . However, further research was needed to confirm this antitumor potential and correlate the respective bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extract from the leaves of M. latecrenata showed antibacterial activity against strains of Staphylococcus aureus, with an MIC value of 100.0 µg/mL [16]. Rodrigues et al [47] also demonstrated that the extract prepared from the leaves of M. latecrenata was promising in inhibiting the bacterial growth of S. aureus and Pseudomonas aeruginosa strains; in addition, it demonstrated synergism with ampicillin and tetracycline, respectively.…”
Section: Antimicrobial Potentialmentioning
confidence: 98%